Radiation dose levels of retrospectively ECG-Gated Coronary CT angiography using 70-kVp tube voltage in patients with high or irregular heart rates - Meyer, Mathias; Haubenreisser, Holger; Meyer, Melissa; Dösch, Christina; Janssen, Sonja; Borggrefe, Martin; Schönberg, Stefan; Henzler, Thomas (Academic radiology, 2017)
Rationale and Objectives Despite ongoing technical refinements, coronary computed tomography angiography (cCTA) remains challenging in its diagnostic value by electrocardiographic (ECG) misregistration and motion artifacts, which commonly occur in patients with atrial fibrillation and high or irregular heart rates. The aim of this study was to evaluate the radiation dose and the number of inconclusive coronary segments at cCTA using retrospective ECG gating at 100 and 70 kV. Materials and Methods With institutional review board approval, 154 patients (median age 54 years, 98 men) with high or irregular heart rate prospectively underwent retrospectively ECG-gated cCTA without tube current modulation on a third-generation dual-source computed tomography (DSCT) system at 70 kV (n = 103) or on a second-generation DSCT system at 100 kV (n = 51). Images were reconstructed in best diastolic phase (BDP), best systolic phase (BSP), and in all phases (APs) at 10% intervals across the R-R cycle. Objective and subjective image qualities were evaluated as well as the presence of motion artifacts with the three different reconstruction approaches. Results The mean heart rate was 93 ± 16 bpm. The mean effective radiation dose was 4.5 mSv for 70 kV compared to 8.4 mSv for 100 kV (P < 0.05). At BDP reconstruction, 71% (n = 110) of the patients showed motion artifacts in one or more coronary segments. At BSP reconstruction, the number of patients with motion artifacts decreased to 37% (n = 57). In contrast, if images were reconstructed with the AP approach, all vessels and coronary segments were evaluable with both cCTA protocols. Conclusions Retrospectively ECG-gated cCTA at 70 kV results in 52% decreased radiation dose. Further using the AP algorithm allowed for diagnostic evaluation of all coronary segments for stenosis, in contrast to BDP or BSP phase alone.
Online 28 October 2016
Gesehen am 29.10.2018